1987
DOI: 10.1002/macp.1987.021881009
|View full text |Cite
|
Sign up to set email alerts
|

A fourier transform infrared and nuclear magnetic resonance study of cyclized natural rubber

Abstract: Fourier transform infrared (FTIR), ' H NMR, and ',C NMR have been used to characterize the structure of natural rubber cyclized with p-toluenesulfonic acid. The samples studied were only partially cyclized. The cyclized portions contained both mobile and rigid domains. Crosslinking occurred during the cyclization reaction. The cyclized samples showed a distribution of functionalities including some oxidation products. All three types of olefinic segmented end groups were formed during cyclization (di-, tri-, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Two spectra regions were observed to undergo changes during cyclization; the carbon-carbon double bond stretching modes at 1600 cm À1 , the CH 2 deformation and CÀ ÀC stretching mode region at 900-1200 cm À1 , and the CÀ ÀH bending mode region at 800-900 cm À1 . 10,21 The band at 1664 cm À1 was due to the cis-1,4 carbon-carbon double bond stretching mode. This observation indicates that cyclization was incomplete.…”
Section: Characterization Of Cyclization Structure Of the Cyclized Namentioning
confidence: 99%
See 1 more Smart Citation
“…Two spectra regions were observed to undergo changes during cyclization; the carbon-carbon double bond stretching modes at 1600 cm À1 , the CH 2 deformation and CÀ ÀC stretching mode region at 900-1200 cm À1 , and the CÀ ÀH bending mode region at 800-900 cm À1 . 10,21 The band at 1664 cm À1 was due to the cis-1,4 carbon-carbon double bond stretching mode. This observation indicates that cyclization was incomplete.…”
Section: Characterization Of Cyclization Structure Of the Cyclized Namentioning
confidence: 99%
“…Patterson and Koenig 10 have investigated the structure of cyclized NR obtained from p-toluenesulfonic acid in toluene solution by FTIR and NMR spectroscopies. They concluded that the cyclized portions contained both mobile and rigid domains due to crosslinking during the cyclization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The broad signals appeared due to the presence of complicated structural units in the polymer after sulfonation of the DPNR. According to a previous study, the overlapping broad signals in the aliphatic region ranging from 10 ppm to 80 ppm were assigned to methyl and methylene carbons of cyclized cis-1,4-isoprene units, and that in the olefinic region ranging from 110 ppm to 155 ppm were assigned to the olefinic methine and trisubstituted carbons [14]. Thus, the broad signals in the 13 C CP/MAS NMR spectrum for the SDPNR-graft-PS were assigned to the cyclized cis-1,4-isoprene units and the sulfonated PS units.…”
Section: Resultsmentioning
confidence: 99%
“…The available proton adds to a double bond, according to Markownikoff's rule, to form a carbenium ion, and subsequently, the carbenium ion attacks the adjacent olefinic carbons, which leads to a cyclic molecular structure after deprotonation, as illustrated in Scheme 1. 5 Harita et al illustrated that fluorine-contained substituted sulfonic acid compounds can be applied as catalyst for the cyclization of conjugated diene polymers. 6 These sulfonic acids are represented by the formula:…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The acid-catalyzed cyclization reaction is a cationic reaction. The available proton adds to a double bond, according to Markownikoff's rule, to form a carbenium ion, and subsequently, the carbenium ion attacks the adjacent olefinic carbons, which leads to a cyclic molecular structure after deprotonation, as illustrated in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%